Designing fatigue-resistant engineered cementitious composites - Qiu, Jishen (2016)
Engineered cementitious composites (ECC) represent a novel type of fiber-reinforced cement-based material with ultra-high ductility. While it emerges in a wide range of infrastructures, including road surface and bridge deck, it encounters premature failure under fatigue loading. This thesis proposes a novel design approach to enhance the fatigue resistance of ECC. Specifically, the premature fatigue failure of ECC can be mitigated, and the fatigue life of ECC is greatly extended. The proposed design approach is based on the development of a new ECC fatigue theory: the fatigue-dependency of ECC, from the components on the micro-scale to the composite behavior on the macro-scale, is characterized by experiment; the fatigue-dependency is then quantified by a micromechanics-based model, which successfully predicts ECC behavior under fatigue loading. After the establishment of the new fatigue theory, two tailoring techniques, i.e. developing high flexural strength and engaging robust self-healing behavior, are practically conducted under the guidance of the theory. These two tailoring techniques successfully improve the fatigue resistance of ECC. The proposed design approach represents a multi-scale tailoring methodology against the fatigue, which can be extended to other composite materials.